Experimental Study of the Effect of Core Stability Training on Body Stability when Performing Gyaku Tsuki on FIKK UNM Students (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to investigate the effect of an eight-week core stability training (CST) program on body stability during the execution of gyaku tsuki among students of the Faculty of Sports Science and Health (FIKK), Universitas Negeri Makassar. Thirty participants were randomly assigned to either an experimental group (n = 15), which underwent CST, or a control group (n = 15), which did not receive any specialized intervention. The training was conducted three times per week for 45–60 minutes, incorporating both static (plank, side plank, bird dog) and dynamic (medicine ball twist, TRX knee tucks, Swiss-ball jackknife) exercises. Body stability was assessed using motion analysis, focusing on trunk control and centre of mass deviations. The experimental group demonstrated a significant improvement from the pre-test (M = 72.40, SD = 4.25) to the post-test (M = 81.33, SD = 3.89), with a paired sample t-test result of p < 0.001. In contrast, the control group showed no significant difference (p = 0.078). An independent t-test comparing post-test scores between groups showed a significant difference (p < 0.001), with a very large effect size (Cohen’s d = 2.20). The findings confirm that CST is an effective method to enhance body stability during gyaku tsuki performance. This supports its integration into karate training programs to improve athletic performance and movement efficiency.